HERUSTIK, HERMENEUTIK SEMIOTIKA MICHAEL RIFFATERRE: (Analisis QS. Ali-Imran: 14) - Luthfi Maulana (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
Heuristic and hermeneutic is the theoretical framework of Michael Rifatere’s analysis which is usedto criticize and explore the meaning of literature. In its relationship with Q.S analysis. al-Quran, itis intended to examine the meaning of the text itself, from before only interpreted at the heuristicstage and then developed analyzed using hermeneutic meaning. In the process of development, themeaning of the Koran text, especially Q.S. A<li-Imran (3): 14 will give birth to various dynamics of themeaning behind the verse until how the meaning of the verse speaks with koledor maqasid ayat. Thisresearch was felt important because in previous studies it was still rarely found which discussed theheuristic and hermeneutic analysis of Michael Riffatre to analyze the verses of the Koran, especiallyQS. ali-Imron: 14. Because in general previous writings only focused on the analysis of literary workssuch as poetry (Faruk, 1996), love poems (Mirantin, 2018) and other literary works such as poetry(Arfan, 2013), (Muchti , tt), (Syafeti, tt) and extracting meaning in various other literary worksincluding mantra (Uniawati, 2017)